Insights into agricultural practices at the Phoenician site of Castro Marim between 7th-5th century BCE - Paladugu, Roshan; Celant, Alessandra; Jha, Gopesh; Di Rita, Federico; de Sousa, Elisa; Arruda, Ana Margarida; Maurer, Anne-France; Magri, Donatella; Barrocas Dias, Cristina (Frontiers in Environmental Archaeology, 2024)
Castro Marim is an Iron Age site from the Algarve region, Portugal. The earliest evidence of settlement, from the Late Bronze Age, dates to the 9th century BCE, with the Phoenician-Punic period dating from the 7th to the 3rd century BCE. This study focuses on the stable isotope analysis of plant and collagen of faunal remains to reconstruct cultivation and husbandry practices. Barley was the most abundantly cultivated cereal crop. The stable isotope results of barley indicate that the primary source of water was natural precipitation and the soil nitrogen was enriched through manuring. Δ13C and δ15N isotope values of stone pine support the previously suggested human management hypothesis. The differences from stable isotope data of domesticated fauna indicate a diverse management strategy for different species based on their economic importance to capitalize from the animal by-products such as wool and dairy products.